2013
DOI: 10.1074/jbc.m113.501585
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for Phospholamban Inhibition of the Calcium Pump in Sarcoplasmic Reticulum

Abstract: Background: Phospholamban (PLB) regulates sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA) activity and is thus a key regulator of cardiac contractility. Results: We present the crystal structure of SERCA in complex with PLB at 2.8-Å resolution. Conclusion: PLB stabilizes a divalent cation-free conformation of SERCA with collapsed Ca 2ϩ binding sites. We call the structure E2-PLB. Significance: The E2-PLB structure explains how PLB decreases Ca 2ϩ affinity and depresses cardiac contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
169
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(190 citation statements)
references
References 50 publications
18
169
0
Order By: Relevance
“…4D), indicating an increase in the apparent affinity for SERCA. The observed increase in SERCA binding is in harmony with previous reports that suggest increased inhibitory potency for this mutant (54,55).…”
Section: Mutation Of Plb C-terminal Residues Alters Regulatory Complesupporting
confidence: 80%
“…4D), indicating an increase in the apparent affinity for SERCA. The observed increase in SERCA binding is in harmony with previous reports that suggest increased inhibitory potency for this mutant (54,55).…”
Section: Mutation Of Plb C-terminal Residues Alters Regulatory Complesupporting
confidence: 80%
“…There is a high degree of sequence homology in the transmembrane regions of PLN and SLN, suggesting a similar mode of interaction with SERCA (6,7). Although studies have demonstrated that PLN and SLN use distinct structural elements and mechanisms to regulate SERCA (8,9), crystal structures of the SERCA-SLN (10,11) and SERCA-PLN (12) complexes are remarkably similar to one another.…”
mentioning
confidence: 84%
“…10). In the reported structure of the SERCA-PLN complex (12), Lys 27 and Asn 30 have been mutated to alanine and cysteine, respectively, and these two residues sit below the positive charge cluster on SERCA. Nonetheless, Lys 27 in human PLN is an asparagine in zfPLN and most mammalian species, so it is unlikely that this change has an effect on SERCA inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting electrochemical gradient supplies most of the driving force for passive Ca 2ϩ efflux into the cytosol during contraction (1). In cardiac sarcoplasmic reticulum, SERCA forms a complex with its 52-amino acid peptide inhibitor, phospholamban (PLB) (1)(2)(3)(4). It has been shown that an increase in the ratio of unphosphorylated phospholamban (U-PLB) to SERCA (by overexpression of PLB, decreased PLB phosphorylation, or decreased SERCA expression) decreases the apparent Ca 2ϩ affinity of SERCA (i.e.…”
mentioning
confidence: 99%